Biosensor for rapid detection of SARS-CoV-2 in real-world samples - Forinova, Michala; Pilipenco, Alina; Visova, Ivana; Kuncak, Jakub; Lynn, N. Scott; Yudin, Petr; Dostalek, Jakub; Honig, Vaclav; Palus, Martin; Maskova, Hana; Dycka, Filip; Sterba, Jan; et al. (Proceedings of IEEE Sensors ..., 2021)
The current COVID-19 pandemic has become a worldwide problem with more than 169 million people infected by May 2021. Here we demonstrate a unique technology, based on the quartz crystal microbalance method, for the rapid detection of SARS-CoV-2. This biosensor fulfils all of the many requirements for the rapid detection of SARS-CoV-2 in complex samples. This is achieved by a tailored antifouling surface post-modified with antibodies against SARS-CoV-2 nucleocapsid protein (N). The A-QCM profits from absence of sample pre-treatment and utilizes the natural properties of N protein, which forms complexes with vRNA. Thanks to this, the clinically relevant LOD of 6.7×10 3 PFU/mL was reached using one-step detection assay. The A-QCM biosensor was also validated with clinical samples (i.e. nasopharyngeal swabs) with full agreement with qRT-PCR. The A-QCM biosensor was also utilized for the presence of SARS-CoV-2 in surface swabs in means of public transport.